1995
DOI: 10.1159/000292322
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Activity in Patients with Invasive Cervical Carcinoma: Importance of a Longitudinal Evaluation in Follow-Up

Abstract: Objective: To analyze longitudinally the basal natural killer cell activity in patients with invasive cervical carcinoma, the natural cytotoxicity was related to the most important known prognostic factors, and evaluated with respect to the clinical outcome of cervical disease. Materials and Methods: Forty-six patients with histologically proven invasive cervical carcinoma treated and followed at the Institute of Gynecology and Obstetrics, Ancona University, Salesi Hospital, were consecutively recruited from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…In humans, numerous studies have demonstrated the prognostic significance of preoperative NK cell activity of patients with colorectal carcinoma and other tumour entities [22][23][24]. Additionally, it was shown that progression of disease of patients with cervix carcinoma was preceded by a decrease of NK cell activity [25]. Therefore, adoptive NK cell therapies are presently under investigation [26].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, numerous studies have demonstrated the prognostic significance of preoperative NK cell activity of patients with colorectal carcinoma and other tumour entities [22][23][24]. Additionally, it was shown that progression of disease of patients with cervix carcinoma was preceded by a decrease of NK cell activity [25]. Therefore, adoptive NK cell therapies are presently under investigation [26].…”
Section: Discussionmentioning
confidence: 99%
“…RNA concentration and quality was determined by spectrophotometry (NanoDrop ND-100). Twohundred nanograms of RNA were reverse-transcribed using the SuperScript TM First-Strand Synthesis system for RT PCR (Invitrogen, Karlsruhe, Germany) choosing Oligo (dT) [12][13][14][15][16][17][18] Primer in a final volume of 20 ll. To exclude false positive results due to contaminating genomic DNA, samples without reverse transcriptase were included.…”
Section: Rna Extraction Reverse Transcription and (Real-time-) Pcrmentioning
confidence: 99%
“…Accumulation of intratumoral NK cells in solid tumors including colorectal cancer, 15 gastric cancer 16 and squamous cell lung cancer 17 was correlated with improved survival rates. In cervical cancer, early studies by Garzetti et al 18 reported an inverse relationship between NK cell activity and disease stage. NK cells, isolated from blood of patients with most advanced tumors (Stage IV), showed the lowest levels of cytotoxicity against the NK cell target cell line K562.…”
mentioning
confidence: 99%
“…Dies kann als Merkmal für Entzündungsreaktionen durch den Tumor gewertet werden, obwohl auch ein Tumor selbst durch Produktion von G-CSF eine Leukozytose induzieren kann [5]. Dieser Anstieg von Granulozyten und Monozyten ist im Durchschnitt bei Probanden der Gruppe 3 etwas geringer vorhanden, bei den Rezidivpatienten (Gruppe 4) jedoch wieder stärker ausgeprägt, ist also in allen Probandengruppen mit Karzinompatienten angehoben und korreliert mit aktivem Tumor durch besondere Erhöhung.…”
Section: Leukozyten Granulozyten Monozytenunclassified